TYPOLOGY AND FUNCTIONS OF POLITICAL CONSULTING - Свирид, З.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
This paper examines different approaches tounder standing the typology of political consulting. The article outlines national model of political advice and typesof subject sexpose dinternal and external political consulting. It  has  been  defined a specific character of professional political consultants in the world and considered a rangeo ffunctions of political consultationin policy.